2022
DOI: 10.3892/ijo.2022.5337
|View full text |Cite
|
Sign up to set email alerts
|

Spine‑specific downregulation of LAPTM5 expression promotes the progression and spinal metastasis of estrogen receptor‑positive breast cancer by activating glutamine‑dependent mTOR signaling

Abstract: Estrogen receptor-positive (ER + ) breast cancer (BC) is a malignancy that is prone to metastasis to the spine, which is difficult to treat and often results in poor prognosis. However, the mechanism underlying the tumorigenesis and spinal metastasis of ER + BC remains unclear. Lysosomal protein transmembrane 5 (LAPTM5) has been reported as a tumor suppressor in several types of cancer, but its role in ER + BC has not been described. Here, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…CX3CL1 is originally translated as a transmembrane protein but can be proteolytically processed to produce a soluble chemokine and has been demonstrated to signal via its receptor CX3CR1 [ 16 ]. More specifically, a high level of CX3CL1 has been revealed to inhibit the expression of lysosomal protein transmembrane 5, explaining how estrogen receptor-positive breast cancer metastasized to the spine [ 17 ]. Furthermore, the expression of CX3CL1 and CX3CR1 in GC tissues was higher than those in adjacent tissues and was promoted in GC tissues from the perineural invasion-positive group compared to the perineural invasion-negative group [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…CX3CL1 is originally translated as a transmembrane protein but can be proteolytically processed to produce a soluble chemokine and has been demonstrated to signal via its receptor CX3CR1 [ 16 ]. More specifically, a high level of CX3CL1 has been revealed to inhibit the expression of lysosomal protein transmembrane 5, explaining how estrogen receptor-positive breast cancer metastasized to the spine [ 17 ]. Furthermore, the expression of CX3CL1 and CX3CR1 in GC tissues was higher than those in adjacent tissues and was promoted in GC tissues from the perineural invasion-positive group compared to the perineural invasion-negative group [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous study found that LAPTM 4 beta (LAPTM4B), which belongs to the same lysosomal membrane protein as LAPTM5, was upregulated in breast cancer, and its high expression was positively related to TNM stage and lymph node metastasis (33). Recently, Meng et al (34) found that LAPTM5 regulated the development and spinal metastasis of ER-positive breast cancer through the glutamine-dependent mTOR signaling, while the present study demonstrated that LAPTM5, which is affected by the transcription factor FOXP3, could contribute to the tumor progression of breast cancer via the Wnt/β-catenin signaling pathway (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…The reported articles did not analyze the specific sites of bone metastases. We found that the weight-bearing bone (spine, 26 cases) was the most common site of metastasis, which may be because the level of CXC3L1/CXC3R1 in the spine bone is higher than that in other bones, which can promote the adhesion and migration of breast cancer cells ( 13 ).…”
Section: Discussionmentioning
confidence: 99%